Rapamycin protects dopaminergic neurons against rotenone-induced cell death in primary mesencephalic cell culture - Radad, Khaled; Moldzio, Rudolf; Rausch, Wolf-Dieter (Folia Neuropathologica, 2015)
Introduction : Parkinson’s disease is the most common movement disorder, characterized by a progressive and extensive loss of dopaminergic neurons in the substantia nigra pars compacta and their terminals in the striatum. So far, only symptomatic treatment is available, and no cure or disease-modifying drugs exist. The present study was designed to investigate the neuroprotective effect of rapamycin, an autophagy inducer, on dopaminergic neurons against rotenone-induced cell death in primary mesencephalic cell culture. Material and methods : Primary mesencephalic cell cultures were prepared from embryonic mouse mesencephala (OFI/SPF, Vienna, Austria) at gestation day 14. Four sets of cultures were treated as follows: one was run as an untreated control, a second one was treated with 20 nM rotenone on the 10th day in vitro (DIV) for 48 h, a third one was co-treated with 20 nM rotenone and rapamycin (1, 10, 100, 1000 nM) on the 10th DIV for 48 h, and a fourth one was treated with rapamycin alone (1, 10, 100, 1000 nM) on the 10th DIV for 48 h. On the 12th DIV, cultures were subjected to immunohistochemistry against tyrosine hydroxylase and to fluorescence staining using LysoTracker Deep Red, JC-1 and DAPI stains. Results : Exposure of such cultures to 20 nM rotenone on the 10th DIV for 48 h reduced the number of dopaminergic neurons by 41% and increased the release of lactate dehydrogenase (LDH) by 178% above untreated controls. Rapamycin (1, 10, 100, 1000 nM) added together with rotenone from the 10th to 12th DIV spared dopaminergic neurons by 17% and reduced the release of LDH by 64% at the concentration of 100 nM compared to rotenone-treated cultures. Activation of an autophagic process by rapamycin was demonstrated by LysoTracker Deep Red fluorescent dye, as indicated by a shift to increased red fluorescence. Rapamycin also significantly elevated the mitochondrial membrane potential (Δψm), as shown by an increase of the red:green fluorescence ratio of JC-1. Increased apoptotic cell death due to rotenone was lowered by rapamycin, as shown by the blue-fluorescent DAPI nucleic acid stain. Conclusions : Our study indicates for the first time that rapamycin, known as an autophagy inducer, protected dopaminergic neurons against rotenone-induced cell death in primary mesencephalic cell culture.